Upaya Pemanfaatan Umbi Bawang Sabrang (Eleutherine americana, MERR) sebagai Zat Warna Alam Untuk Pencelupan Kain Selulosa dan Poliamida - Kuntari Adi Suhardjo; Sasas Barkasih (Center for Pulp and Paper, 2005)
In line with the Indonesian natural resource exploration, there has been a research on cellulose and polyamide fabrics dyeing by natural pigment of Onion Bulb Sabrang. The Dyeing of cellulose fabrics is carried out in neutral condition and alkaline condition (pH=11), whereas the polyamide fabrics dyeing is carried out in neutral and acid condition (pH=5). The dyeing times are varied to 30, 45 and 60 minutes in boiling condition. After dyeing is followed by the addition of K2Cr2O3 (Kalium bichromate), Alum (Al2SO4.18 H2O), and Saline Red B in solution of 1, 2 and 3 g/l. The dyeing result is tested upon the color absorbed, color discrepancy between dyeing and before and after a three months pigment storage, color removal upon washing, rubbing, sweating and sun exposing. Data evaluation shows that natural pigment of onion bulb Sabrang can be used as coloring agent for cellulose and polyamide fabrics. Color removability upon washing, sweating, and sun exposing is bad, but it can be strengthen by the addition of Kalium bichromate, Alum, and Saline Red B. Nevertheless, color removability upon rubbing is good . The dyeing result of polyamide fabrics is better than cellulose fabrics.